Respuesta :
Answer:
a. and e.
Step-by-step explanation:
Hello, there are two ways to handle this kind of question.
... Either you solve the equation ...
[tex]x^2+4x-9=x+1\\\\x^2+3x-10=0\\\\x^2-2x+5x-10=x(x-2)+5(x-2)=(x+5)(x-2)=0\\\\x= -5 \ \ or \ \ x = 2[/tex]
So the right answers are a. and e.
... Or, you check which answer can be right.
We replace x by 2 and the two expressions are equal.
[tex]2^2+4*2-9=4+8-9=3 \ and \ 2+1=3[/tex]
So this is a. 2
We replace x by 4 and the two expressions are not equal.
[tex]4^2+4*4-9=16+16-9=23 \ and \ 4+1=5[/tex]
So this is not b. 4
We replace x by -7 and the two expressions are not equal.
[tex]7^2-4*7+9=49-28+9=30 \ and \ -7+1=-6[/tex]
So this is not c. -7
We replace x by -3 and the two expressions are not equal.
[tex]3^2-4*3-9=9-12-9=-12 \ and \ -3+1=-2[/tex]
So this is not d. -3
We replace x by -5 and the two expressions are equal.
[tex]5^2-4*5-9=25-20-9=-4 \ and \ -5+1=-4[/tex]
So this is e. -5
We replace x by -4 and the two expressions are not equal.
[tex]4^2-4*4-9=16-16-9=-9 \ and \ -4+1=-3[/tex]
So this is not f. -4
Thank you.